2023
DOI: 10.1159/000531261
|View full text |Cite
|
Sign up to set email alerts
|

Association of Self-Reported Nighttime Sleep Duration with Chronic Kidney Disease: China Health and Retirement Longitudinal Study

Abstract: <b><i>Introduction:</i></b> The cohort study aimed to assess the association of nighttime sleep duration and the change in nighttime sleep duration with chronic kidney disease (CKD) and whether the association between nighttime sleep duration and CKD differed by daytime napping. <b><i>Methods:</i></b> This study included 11,677 individuals from the China Health and Retirement Longitudinal Study (CHARLS) and used data from the 2011 baseline survey and four follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…On the other hand, biological mechanisms linking long sleep duration to CKD are unknown and even remain elusive in CVD, warranting more attention. Unique to Jiang et al [14], daytime napping was found to offset the excess risk of CKD portended by short sleep duration. This parallels experimental work, which demonstrates that extreme nocturnal sleep restriction, when supplemented with daytime nap opportunity, does not increase urinary norepinephrine excretion compared to normal sleep opportunity [17].…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…On the other hand, biological mechanisms linking long sleep duration to CKD are unknown and even remain elusive in CVD, warranting more attention. Unique to Jiang et al [14], daytime napping was found to offset the excess risk of CKD portended by short sleep duration. This parallels experimental work, which demonstrates that extreme nocturnal sleep restriction, when supplemented with daytime nap opportunity, does not increase urinary norepinephrine excretion compared to normal sleep opportunity [17].…”
mentioning
confidence: 98%
“…In this issue of the American Journal of Nephrology , Jiang et al [14] report an association between sleep duration and CKD in a large sample of mid-life and older Chinese adults from the China Health and Retirement Longitudinal Study (CHARLS; n = 11,677). Unique to the present study, a novel assessment of temporal sleep pattern stability was obtained through repeated surveys over a 7-year follow-up period.…”
mentioning
confidence: 99%
See 3 more Smart Citations